IMPROVEMENT OF ELECTRONIC SOFTWARE AND METHODICAL SUPPORT OF MATERIALS SCIENCE (Scientific journal of the Fergana State University, 2024)
The article presents 3D animations, virtual reality design, mathematical modeling, information representation theory, computer environment, prepared on topics that students cannot imagine from the subject "Materials Science (Materials Science and Construction Materials)" in the block of general professional sciences. Information about the development of an electronic textbook based on the basic principles of perception is given